A Bibliometric Analysis of the Top 100 Most Cited Chronotype Research Papers. (27th January 2017) - Norbury, Ray
Bibliometric indices are a widely used measure of research impact. The aim of the current study was to identify and characterise the top one hundred most-cited research articles in the topic of chronotype research. A search of the Thomson Reuters Web of Science database returned 974 eligible articles (published between 1990 and 2016). Citations for the 100 most-cited articles ranged between 438 and 29. The most represented journal was Chronobiology International ( n = 30). Nearly 50% of articles originated in Germany and the U.S. The bibliometrics reported identify key publications and provide insight into trends within the topic of chronotype research.